2001
DOI: 10.1007/978-94-017-3674-9_66
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of the Period Immediately Preceding Anthesis for Grain Weight Determination in Wheat

Abstract: Although individual grain weight is an important source of variation for grain yield, there is still poor understanding of the causes determining final grain weight. Almost all studies conducted for understanding the determinants of grain weight have been focused on the post-anthesis period. However, there is important evidence that preanthesis conditions could also modify final grain weight. Three experiments including different sowing dates, genotypes and temperature regimes between booting and anthesis, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 14 publications
6
66
0
3
Order By: Relevance
“…Individual seed weight was sensitive during a period from before flowering to 140% of flowering time corresponding to maturity. This result matched with Calderini et al (1999Calderini et al ( , 2001, who demonstrated that the period when the carpels (which will become the external structures of the grain) grow determines the final individual grain weight. The number of spikes was sensitive during a late period from 80% to 130% of flowering time, suggesting that the most sensitive process was probably not tillering itself, which occurs earlier, but rather tiller abortion around flowering.…”
Section: Relevance Of the Periods Of Sensitivities Calculated In The supporting
confidence: 80%
“…Individual seed weight was sensitive during a period from before flowering to 140% of flowering time corresponding to maturity. This result matched with Calderini et al (1999Calderini et al ( , 2001, who demonstrated that the period when the carpels (which will become the external structures of the grain) grow determines the final individual grain weight. The number of spikes was sensitive during a late period from 80% to 130% of flowering time, suggesting that the most sensitive process was probably not tillering itself, which occurs earlier, but rather tiller abortion around flowering.…”
Section: Relevance Of the Periods Of Sensitivities Calculated In The supporting
confidence: 80%
“…Appearance of high temperature stress at anthesis reduced grain number per ear and harvest index (Ugarte et al 2007). High temperature during the period that precedes anthesis reduces grain weight, as the consequence of negative temperature effects on carpel growth that occur in time of anthesis (Calderini et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increased TGW in 1BL/1RS lines was accompanied by increased SPAD and AWL. However, in wheat where grain-filling is mostly sink-limited (Borrás et al 2004), reductions in grain number cannot be compensated by grain Cereal Research Communications 43, 2015 weight (Calderini et al 2001;Ugarte et al 2007). Despite increased TGW in present study, 1BL/1RS class had lower grain yield due to decreased grain number.…”
Section: Discussionmentioning
confidence: 99%